AB0371 Clinical Significance of Anti-Adalimumab Antibodies in Rheumatoid Arthritis, Ankylosing Spondilitis and Psoriasic Arthritis. (10th June 2014) - Hoxha, A.; Calligaro, A.; Tonello, M.; Carletto, A.; Paolazzi, G.; Bortolotti, R.; Felicetti, M.; Ramonda, R.; Del Ross, T.; Grava, C.; Boaretto, M.; Favaro, M.; et al.
Abstract : Background: The generation of antidrug antibody (ADAb) is increasingly recognised as a mechanism explaining the failure of anti-TNF drugs in chronic inflammatory diseases. Objectives: We designed a prospective, multicentre study on antibodies against adalimumab (anti-ADA) in a cohort of patients treated with adalimumab and affected with rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriasic arthritis (PsA), to evaluate their clinical significance. Methods: Fifty-eight consecutive patients were enrolled from four Italian Rheumatology Centres. Twenty-one (36.2%) were affected by RA, 22 (37.9%) by AS and 15 (25.9%) by PsA respectively. Anti-ADA antibodies were tested using ELISA commercial kits, kindly provided by Technogenetics, Italy, following the manufacter's instructions. Moreover, anti-nuclear antibodies (ANA), anti-dsDNA antibodies, anti-estraible nuclear antigen (anti-ENA) and anti-phospholipid antibodies (aPL) were determined. Detection was made at baseline, 4, 12 and 24 weeks of therapy, respectively. Also, clinimetric (DAS28, BASDAI, BASFI, ASAS20) and serological (rheumathoid factor [RF], anti citrullinated cyclic peptides [ACPA] data were collected at the same intervals. Results: The prevalence of anti-ADA, was 6/21 (28.6%) in RA, 4/22 (18.2%) in AS and 1/15 (6.7%) in PsA patients. Ten of the eleven anti-ADA (90.9%) occurred within the first month of therapy. There was a significant association between anti-ADA and lack of response and/or loss of drug efficacy in RA (OR 2.7, 95% CI: 1.5 - 4.9, p=0.0009), in AS (OR: 2.03, 95% CI 1.1 - 3.6; p=0.02), and in PsA (OR: 743.2, 95% CI 44.30 – 12.468; p<0.0001), respectively. Also, was a significant association between the presence of anti-ADA and the development of adverse events (p<0.0001). Surprisingly, was found a significant association between the positivity of RF and/or ACPA antibodies and the absence of anti-ADA, OR: 0.25, 95% CI: 0.1-0.5, p<0.0001 and OR: 0.3, 95% CI: 0.1-0.6, p=0.0008, respectively. The presence of ANA or anti-ENA was significantly associated with the development of anti-ADA (OR: 2.56, 95% CI 1.42-4.63, p=0.002 and OR: 4.56, 95% CI 2.39-8.67 p<0.0001). While, there was no significantly association between the presence of aPL antibodies and the presence of anti-ADA. No patient developed signs and/or symptoms of connective tissue disease or thrombosis during treatment with ADA. Conclusions: Our study suggests that anti-ADA antibodies may be considered a predictor of the clinical response to ADA and the occurrence of adverse events. It would therefore justified to incorporate the determination of anti-ADA in the monitoring of patients with RA, AS and PsA treated with ADA. In the course of therapy with ADA may also be helpful the determination of ANA and anti-ENA in view of their association with anti-ADA. It remains to confirm whether patients positive for ACPA, because of the association with the absence of anti-ADA, may have a better response to treatment with ADA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5938